2018
DOI: 10.4103/ortho.ijortho_382_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors Responsible for Redisplacement of Pediatric Forearm Fractures Treated by Closed Reduction and Cast

Abstract: Background:Pediatric forearm fractures are still considered an enigma in view of their propensity to redisplace in cast. The redisplacement may be a potential cause for malalignment. We prospectively analyzed the role of risk factors and above casting indices in predicting significant redisplacement of pediatric forearm fractures treated by closed reduction and cast.Materials and Methods:113 patients of age range 2–13 years with displaced forearm fractures, treated by closed reduction and cast were included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 33 publications
6
31
1
Order By: Relevance
“…After reduction and application of the cast, measurements on plain radiographs can be made and if needed, and the cast can be adjusted to reduce the risk of redisplacement. Even though the Cast Index is easier to measure, the Three-Point Index was found to be superior in predicting redisplacement when compared to the Cast Index (sensitivity 94.7%, specificity 95.2%, NPV 98.4%, PPV 85.7% for Three-Point Index and sensitivity 63.2%, specificity 52.4%, NPV 82.5%, PPV 28.6% for Cast Index) with high inter-and intra-observer reliability (intra class correlation coefficient 0.99) [18,19]. The studies included in the present meta-analysis reported redisplacement rates between 9.7% and 35% after reduction and cast immobilization of displaced distal radius fractures in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After reduction and application of the cast, measurements on plain radiographs can be made and if needed, and the cast can be adjusted to reduce the risk of redisplacement. Even though the Cast Index is easier to measure, the Three-Point Index was found to be superior in predicting redisplacement when compared to the Cast Index (sensitivity 94.7%, specificity 95.2%, NPV 98.4%, PPV 85.7% for Three-Point Index and sensitivity 63.2%, specificity 52.4%, NPV 82.5%, PPV 28.6% for Cast Index) with high inter-and intra-observer reliability (intra class correlation coefficient 0.99) [18,19]. The studies included in the present meta-analysis reported redisplacement rates between 9.7% and 35% after reduction and cast immobilization of displaced distal radius fractures in children.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve articles that met the inclusion criteria and reported on similar age groups and definitions for redisplacement were included in this meta-analysis ( Fig. 2) [5,7,18,19,[25][26][27][28][29][30][31][32]. Table 1 shows the characteristics of the twelve included studies.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…These are: translation of bone fragments more than 50% in each plane, the patient's age above 9 y.o., complete radial fracture, and angulation of the radius > 15° on lateral radiographs and of the ulna >10° on AP radiographs [13]. A similar analysis was carried out by Arora et al who evaluated 113 patients [8]. In their study, they did not link late complications with any characteristics of the population under study.…”
Section: Discussionmentioning
confidence: 87%
“…Kemal K et al 11 in their study comprising of children between 6-15 years, found the mean age to be 8.6 years. Flynn JM et al 7 had a mean age of 9.5 years while Arora R et al 12 had a mean age of 8.62 years in their respective studies. In the present study, there were 17 boys (60.71%) and 11 girls (39.29%).…”
Section: Discussionmentioning
confidence: 97%